EMILY DICKINSONS' DISAPPOINTMENT TOWARD PURITANISM TEACHINGS REFLECTED IN I PRAYED AT FIRST A LITTLE GIRL - PURNOMO, SISWO; WIDYANINGRUM, AGNES (English Literature Department, Faculty of Economics, Law, and Humanities, 2023)
Poetry is a unique way to express someone's feelings. Sometimes the poetry is the author's experience. Emily Dickinson was an American poet woman who wrote a lot of religious poetry. In this study, the researchers try to analyze her expression in I Prayed at First a Little Girl. The aims of this study are to know the psychological side of Emily Dickinson toward Puritanism in her poetry I Prayed at First a Little Girl, to know the influence of the social condition of the society toward Emily Dickinson's poetry, and to know the meaning of Emily Dickinson's poetry mentioned above. The method of collecting data which the researchers used is the library research method, in which various sources are collected and also used to support the discussion. In approaching the poetry, the researchers use the objective or the structural approach method and psychological approach method to get deeper understanding of the author's characteristics. After analyzing the poetry, the researchers concluded that the poetry was the expression of Emily Dickinson disappointment toward Puritanism teachings. Emily was disappointed with her father and the priests in her church who asked her to obey all their rules since she was a child without giving any chance to ask about them.